Estudo de dosagem de tijolos de solo-cimento com adição de resíduos de construção e demolição - da Silva Segantini, Antonio Anderson [UNESP]; Wada, Patrycia Hanna [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2011)
An evaluation of the composition of soil cement bricks with construction and demolition waste. Sustainable development requires the existence of a production network that includes the reuse of construction waste for new materials. Current analysis investigates an optimal soil-cement composition made up of construction and demolition waste for the manufacture of pressed bricks. Soil-cement bricks were manufactured from construction and demolition wastes (CDW), A-4 classified fine sandy soil and cement CP II Z 32. Laboratory tests, comprising test compaction, optimum water content and maximum dry specific weight, consistency limits, grain size distribution and linear shrinkage, were made to characterize the materials researched. Compressive strength and absorption tests were also undertaken in different combinations of composition. Results showed that the application of CDW improved soil-cement qualities and reduced shrinkage of the material used.
An evaluation of the composition of soil cement bricks with construction and demolition waste
Keywords: construction material; sustainable development; recycling; reuse